Penerapan Metode Waterfall Dalam Membangun Aplikasi Pemberitahuan Tanggal Jatuh Tempo Piutang Outlet Pada PT Bintang Suryasindo - Aprizal, Yarza; Mahmud; Jhonsen Syaftriandi, Muhammad; Hidayat, Feby (CV. Multi Kreasi Media, 2024)
PT Bintang Suryasindo, a company focusing on the distribution of consumer products, caters to a diverse customer base, including outlets spread across various regions. One crucial aspect of company operations is the management of receivables originating from these outlets. To facilitate its business operations, PT Bintang Suryasindo provides credit or receivable facilities to outlets. However, in its implementation, customer outlets often struggle to recall or monitor the receivable payment deadlines they must meet. Therefore, an effective solution is required to provide timely notifications to outlets. One viable solution is to develop an application capable of sending receivable notifications directly to outlets. The application, built using the Waterfall method, incorporates features such as employee task schedules, settled outlets, and overdue outlets. The results of testing for all 18 test cases were successful and aligned with the testers' expectations. This indicates that the application is ready for implementation.